Development and validation of risk prediction equations to estimate future risk of blindness and lower limb amputation in patients with diabetes: cohort study - Hippisley-Cox, Julia; Coupland, Carol (BMJ Publishing Group, 2015)
Study question: Is it possible to develop and externally validate risk prediction equations to estimate the 10 year risk of blindness and lower limb amputation in patients with diabetes aged 25-84 years?